1995
DOI: 10.1002/ptr.2650090618
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antiulcer activity of Moringa oleifera leaf extract on gastric ulcer models in rats

Abstract: The methanol fraction of M. oleifera leaf extract was found to possess significant protective actions in acetylsalicylic acid, serotonin and indomethacin induced gastric lesions in experimental rats. A significant enhancement of the healing process in acetic acid-induced chronic gastric lesions was also observed with the extract-treated animals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 3 publications
2
77
0
1
Order By: Relevance
“…Aqueous leaf extracts also showed antiulcer effect (Pal et al, 1995a) indicating that the antiulcer component is widely distributed in this plant. Moringa roots have also been reported to possess hepatoprotective activity (Ruckmani et al, 1998).…”
Section: Antispasmodic Antiulcer and Hepatoprotective Activitiesmentioning
confidence: 88%
See 2 more Smart Citations
“…Aqueous leaf extracts also showed antiulcer effect (Pal et al, 1995a) indicating that the antiulcer component is widely distributed in this plant. Moringa roots have also been reported to possess hepatoprotective activity (Ruckmani et al, 1998).…”
Section: Antispasmodic Antiulcer and Hepatoprotective Activitiesmentioning
confidence: 88%
“…The methanol fraction of M. oleifera leaf extract showed antiulcerogenic and hepatoprotective effects in rats (Pal et al, 1995a). Aqueous leaf extracts also showed antiulcer effect (Pal et al, 1995a) indicating that the antiulcer component is widely distributed in this plant.…”
Section: Antispasmodic Antiulcer and Hepatoprotective Activitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Moringa foliage has been found to increase animal productivity (Foidl et al, 2001;Sá nchez et al, 2006). Pal et al (1995) have reported that the methanol fraction of moringa leaf extract possesses antiulcer activity against gastric lesions induced in rats. Flowers of moringa are considered to possess medicinal value as a stimulant, aphrodisiac, diuretic and cholagogue, and they have been also reported to contain flavonoid pigments such as quercetin, kaempferol, rhamnetin, isoquercitrin and kaempferitrin (Nair and Subramanian, 1962).…”
Section: Plants Containing Multibioactive Compoundsmentioning
confidence: 99%
“…Leaf extracts show hypocholesterolaemic 6 , hypotensive, bradycardic 7 and anti-ulcerative activity 8 . The dry pods are adequate to use as a substratum for laboratory animal bedding 9 .…”
Section: Moringa Oleifera Lamarck (Synonymmentioning
confidence: 99%